Pemetaan Potensi Desa dalam Rangka Mewujudkan Bumdes Di Kecamatan Moyudan - Widiastuti, Harjanti; Kresnawati, Etik; Utami, Evy Rahman (Universitas Muhammadiyah Yogyakarta, 2019)
The founding of Village-Owned Business Entity (Badan Usaha Milik Desa, BUMDes) is a mandate of Laws. It is also one of the leading work programs in Priority Performance in the period 2015-2019. Even though 5000 BUMDes targeted by the Ministry of Villages, Disadvantaged Regions and Transmigration has exceeded by the establishment of nearly 35.000 BUMDes across Indonesia. However, there are some villages which still seem doubtful and less motivated to establish BUMDes. Moyudan sub-district consists of four villages and there is only one village which has already pioneered the establishment of BUMDes. The aim of the community service program (PPM) is to motivate the initiation of the establishment of BUMDes in Moyudan sub-district. The activity of PKM was conducted through initial survey, training, and consultation on the mapping of village potential. The outcome of this activity is the documents of the mapping of village potential and the selection of BUMDes enterprise planning.